A long noncoding RNA LOC103690121 promotes hippocampus neuronal apoptosis in streptozotocin-induced type 1 diabetes. (11th June 2019) - Hao, Lijun; Li, Qian; Zhao, Xin; Li, Yanli; Zhang, Ce
Highlights: STZ-induced diabetic rats developed cognitive dysfunction with neuron apoptosis. STZ-induced diabetes dysregulated 101 lncRNAs including upregulated LOC103690121. Glucose induced hippocampal neuron apoptosis in vitro and LOC103690121 expression. LOC103690121 overexpression enhanced glucose-induced neuron apoptosis. LOC103690121 siRNA impede glucose-induced neuron apoptosis by inhibiting activation of the PI3K/Akt pathway. Abstract: Diabetes related cognitive impairment is a severe complication. The diabetes-induced cognitive impairment is associated with insulin resistance and glucose-induced neuron apoptosis in the brain. We intended to investigate the association of long non-coding RNAs with diabetes-induced cognitive impairment in rats. Here, Type 1diabetes (T1D) rat model was induced using streptozotocin (STZ). The diabetic rats showed significant cognitive dysfunction, with increased latency period to find the hidden platform during morris water maze test. The brain injury and reduced neuronsin STZ-induced diabetic rats was determined using hematoxylin and eosin staining and Nissl's staining. We performed the LncRNA microarray analysis and identified 101 differentially expressed lncRNAs in streptozotocin (STZ)-induced type 1 diabetes (T1D) comparing with control. Among these lncRNA, LOC103690121 was upregulated. in vitro glucose treatment in hippocampal neurons showed LOC103690121 and neuron apoptosis was increased by glucose treatment. Transfection experiments showed LOC103690121 overexpression promoted neuron apoptosis, and its inhibition suppressed glucose-induced apoptosis. Western blot analysis showed that the expression profiles of apoptosis related proteins (cleaved-caspase-3, -8, -9, and Bax) were in line with LOC103690121 expression, while the profiles of Bcl-2 and PI3K/Akt signaling pathway was contrast to LOC103690121 expression. In conclusion, the results of our study confirmed lncRNA LOC103690121 promoted STZ-induced cognitive impairment in diabetic rats by promoting neuron apoptosis through PI3K/Akt signaling pathway.